Characterization of freeze dried and oven dried nitrohumic acids derived from the Mukah coal, Sarawak - Stephanie, Nawang Gayet (Universiti Malaysia Sarawak, UNIMAS, 2007)
Alkaline extraction was used to extract humic acids from Mukah coal. The alkaline solution used to perform this extraction is potassium hydroxide, KOH. Humic acids were extracted via oven-drying and freeze-drying approach. The characterization of oven-dried humic acids and freeze-dried humic acids was conducted by measuring moisture content, ash content, carboxyl group (-COOH), total acidity (COOH phenolic- and/or enolic –OH) and phenolic (-OH). The spectroscopic characterization for both humic acids was done by using FTIR spectroscopy, Scanning Electron Microscopy (SEM) and UV/VIS spectrophotometer. Factorial design was also conducted to determine the factors (temperature, time and concentration) that will affect the yield of humic acids. The study showed that high concentration of alkaline solution (KOH) will give rise to high yield of humic acids. The results of statistical analysis (Paired t-test) show that there was no significant difference in the characteristics between them except for E4/E6 ratio.